2001
DOI: 10.1518/001872001775898223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Navigation Speed on Motion Sickness Caused by an Immersive Virtual Environment

Abstract: This study investigated the effects of navigation speed on the level of motion sickness during and after a 30-min head-steered virtual environment. Root-mean-squares for 8 speeds in the fore-and-aft axis were 3, 4, 6, 8, 10, 24, 30, and 59 m/s. Participants were 96 Chinese men. Both the nausea and vection ratings increased significantly with speeds increasing from 3 m/s to 10 m/s. At speeds exceeding 10 m/s, the ratings stabilized. Navigation speeds were found to significantly affect the onset times of vection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(95 citation statements)
references
References 19 publications
2
91
0
2
Order By: Relevance
“…This seems to be true of both rotational and positional movement. Previous academic research into the relationship between navigation speed and motion sickness in VR has observed a stabilization of nausea ratings at high speeds, but not a drop of the kind that would naturally lead to this conclusion [13]. Other research has simply concluded that infinite velocity techniques (teleportation) cause less discomfort [8].…”
Section: Conclusion: Short Fast Movementsmentioning
confidence: 98%
“…This seems to be true of both rotational and positional movement. Previous academic research into the relationship between navigation speed and motion sickness in VR has observed a stabilization of nausea ratings at high speeds, but not a drop of the kind that would naturally lead to this conclusion [13]. Other research has simply concluded that infinite velocity techniques (teleportation) cause less discomfort [8].…”
Section: Conclusion: Short Fast Movementsmentioning
confidence: 98%
“…In fact, the increase due to immersion is just about 1 unit. This is a small number compared to published results of nausea effects in virtual environments from studies also using the SSQ, e.g., [24] in which reports range up to 3.5. The small increase of the Nausea scale we see due to immersion is consistent with our very infrequent reports of nausea in our virtual environment (system or this experiment?).…”
Section: Discussionmentioning
confidence: 74%
“…Previous research has treated SSQ ratings as interval data [24]. We therefore used parametric statistics for our primary analysis, but also checked our results with nonparametric Mann-Whitney U tests.…”
Section: Resultsmentioning
confidence: 99%
“…All participants had the same exposure time to reduce differences in simulator sickness (So et al, 2001). It is also known that navigation speed affects simulator sickness, being maximal at 10 m/s and stabilizing for faster navigation speeds (So et al, 2001). In our case, participants were able to achieve speeds in the range of 0-7 m/s.…”
Section: Real Flight Testmentioning
confidence: 99%